Hloušekite, (Ni, Co)Cu4(AsO4)2(AsO3OH)2(H2O)9, a new member of the lindackerite supergroup from Jáchymov, Czech Republic. (October 2014) - Plášil, J.; Sejkora, J.; Škoda, R.; Novák, M.; Kasatkin, A. V.; Škácha, P.; Veselovský, F.; Fejfarová, K.; Ondruš, P.
Abstract: Hloušekite, (Ni, Co)Cu4 (AsO4 )2 (AsO3 OH)2 (H2 O)9, is a new supergene arsenate mineral from the Geister vein (Rovnost mine), Jáchymov (St Joachimsthal), Western Bohemia, Czech Republic. It was found along with veselovský ite, pradetite, lavendulan, arsenolite, babánekite and gypsum on the surface of strongly altered ore fragments containing dominant tennantite and chalcopyrite. Hloušekite forms thin, lath-like crystals, locally elongated reaching up to 3 mm across. It is transparent, has a pale green colour with vitreous lustre, has a greyish-white streak and it is very brittle with an uneven fracture. It does not fluoresce under shortwave or longwave ultraviolet radiation. Cleavage on {010} is perfect; the Mohs hardness is 2–3. The calculated density is 3.295 g cm –3 . Hloušekite is optically biaxial with α' = 1.653(2) and γ' = 1.73. The estimated optical orientation is γ' vs. elongation (c) = 14(1)°. In larger grains it is weakly to moderately pleochroic (α = colourless, γ = pale green to green). Hloušekite is triclinic, space group P1̄, a = 6.4010(6), b = 8.0041(6), c = 10.3969(14) Å, α = 85.824(8), β = 79.873(9), γ = 84.655(7)° and V = 521.23(10) Å 3, with Z = 1, a:b:c = 0.800:1:1.299. The eight strongest lines in the powder X-ray diffraction (XRD) pattern [d in Å (I)(hkl)] are 10.211(100)(001), 7.974(9)(010), 3.984(6)(020), 3.656(5)(11̄2), 3.631(5)(02̄ 1), 3.241(5)(022), 3.145(5)(200) and 3.006(5)(210). Chemical analysis by electron microprobe yielded MgO0.20, FeO0.10, NiO 5.79, CoO1.80, CuO29.53, ZnO0.66, Al2 O3 0.14, P2 O5 0.11, As2 O5 45.01, H2 O17.71 (calc.), for a total of 101.05 wt.%. The resulting empirical formula, calculated by stoichiometry (9H2 O + 2OH), obtained from the crystal structure, is (Ni0.79 Co0.25 )Σ1.04 (Cu3.78 Zn0.08 Mg0.05 Al0.03 Fe0.01 )Σ3.95 (AsO4 )1.98 (PO4 )0.02 (AsO3 OH)2.00 (H2 O)9.00 . The ideal endmember formula, NiCu4 (AsO4 )2 (AsO3 OH)2 (H2 O)9.00, requires NiO7.23, CuO30.81, As2 O5 44.51, H2 O17.45, total 100.00 wt.%. The crystal structure of hloušekite was solved by charge flipping from single-crystal XRD data and refined to R 1 = 0.0599 for 1441 reflections with [Iobs > 3σ(I)]. Hloušekite is a new member of the lindackerite group (also including lindackerite, pradetite and veselovský ite) of the lindackerite supergroup. The ondrušite group of the lindackerite supergroup includes ondrušite, chudobaite, geigerite and klajite. The establishment of these two groups reflects the difference between the crystal structures of their members, mainly in the coordination environment of the Me cations.